Virtual mass of an oscillating sphere within a fixed concentric shell - Ackermann, Norbert L., author; Anat, Arbhabhirama, author; Colorado State University, Civil Engineering Section, publisher (Colorado State University. Libraries, 1962)
The virtual mass of a sphere oscillating within a fixed concentric spherical shell filled with water was determined experimentally for seven sphere-to-shell diameter ratios between 0 and 0.865. Laboratory measurements of the virtual mass for diameter ratios less than 0.520 agreed closely with the theoretically predicted values based on a potential flow analysis. For ratios greater than 0.520 the virtual mass increased more rapidly than the potential flow theory indicated with an increase of 33% for a diameter ratio of 0.865.
CER62AA84.
July 30, 1962.
Keywords: Mass transfer -- Mathematical models; Hydraulic models; Viscosity -- Mathematical models; Fluid mechanics